AMP-Activated Kinase Regulates Cytoplasmic HuR - Wang, Wengong (American Society for Microbiology, 2002)
While transport of RNA-binding protein HuR from nucleus to cytoplasm is emerging as a key regulatory step for HuR function, the mechanisms underlying this process remain poorly understood. Here, we report that the AMP-activated kinase (AMPK), an enzyme involved in responding to metabolic stresses, potently regulates the levels of cytoplasmic HuR. Inhibition of AMPK, accomplished either through cell treatment or by adenovirus infection to express dominant-negative AMPK, was found to increase the level of HuR in the cytoplasm and to enhance the binding of HuR to p21, cyclin B1, and cyclin A mRNA transcripts and elevate their expression and half-lives. Conversely, AMPK activation, achieved by means including infection to express constitutively active AMPK, resulted in reduced cytoplasmic HuR; decreased levels and half-lives of mRNAs encoding p21, cyclin A, and cyclin B1; and diminished HuR association with the corresponding transcripts. We therefore propose a novel function for AMPK as a regulator of cytoplasmic HuR levels, which in turn influences the mRNA-stabilizing function of HuR and the expression of HuR target transcripts.